HUGO ASSMANN: DA TEOLOGIA DA LIBERTAÇÃO À EDUCAÇÃO PARA A SOLIDARIEDADE. - SILVA, PEDRO PAULO SOARES DA (2017)
The current paperwork seeks to present an analysis about the theology applied to education, specially the liberation theology to solidarity education, at the Hugo Assmann’s thought. After a long time teaching, giving lectures and researching abroad, Assmann returns to Brasil and brings a knowledge that contributes significantly to the way of understanding the liberation theology, how theology and economics are related and also the relation between theology and education. While discussing education, Assmann reaches beyond the classroom, he also involves the exchange of experiences searching for the preparation for the labor market, for the social solidarity, a search for overcoming the oppressive social inequality and mainly the full development of the individual as a whole, not disregarding his particularities. In order for this to happen, a conversion to solidarity is necessary, which results in the re-enchantment of the education. The good news is, according to Assmann, that educators are also life defenders, not denying the market as such, but giving more attention to the tendency of inclusion than the one of exclusion, aiming for the overcoming of social inequalities. In general, this work has the purpose of studying, from Hugo Assmann's point of view, the relation between theology and education, specially the issues related to spirituality, education and solidarity.